Optical glass with high refractive index and preparation method thereof

By preparing optical glass containing silica, styrene and selenium atoms, a special preparation method is used to form the core-solid structure composite particles of Se-SiO2-PS and melt-combined with other oxides, the problem of insufficient refractive index of existing optical glass is solved, and high refractive index and multiple performance improvements are achieved.

CN119661076AActive Publication Date: 2025-03-21XUZHOU FENGCHENG NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411891662.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

When existing optical glasses face high-precision focusing, imaging or optical signal transmission tasks at specific wavelengths, their refractive index characteristics are insufficient, making it difficult to meet the needs of high-end applications.

Method used

By preparing an optical glass composed of silica, styrene, selenium atoms, sodium oxide, potassium oxide, calcium oxide, barium oxide and lead oxide, a special preparation method is used to form the core-soft structure composite particles of Se-SiO2-PS, and melt and combine them with other oxides at a high temperature to form an optical glass with a high refractive index.

Benefits of technology

It realizes the high refractive index, tensile strength, compressive strength, corrosion resistance and chemical stability of optical glass, and meets the performance requirements of high-end optical instruments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of optical glass, in particular to optical glass with high refractive index and a preparation method thereof. The invention provides optical glass with a high refractive index. The optical glass comprises the following raw materials: silicon dioxide, styrene, selenium atoms, sodium oxide, potassium oxide, calcium oxide, barium oxide and lead oxide. The invention further provides a preparation method of the optical glass with the high refractive index. The preparation method comprises the two steps of S1 composite particle preparation and S2 optical glass preparation. According to the method, composite particles of Se-SiO2-PS shell-core structures can be formed; and synthesizing the optical glass by using the composite particles as a base material. The optical glass obtained by the method has high tensile strength, high compressive strength, high corrosion resistance and chemical stability, and the refractive index of the optical glass is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of optical glass, and in particular to an optical glass with a high refractive index and a preparation method thereof. Background Art

[0002] Optical glass, as the cornerstone material for manufacturing precision optical instruments and key optical components, has high light transmittance, high refractive index and stable optical properties. However, with the rapid development of optical technology, especially in the in-depth application of high-tech fields such as aerospace, medical diagnosis, information and communication, more stringent requirements are put forward for the performance indicators of optical glass. In particular, in terms of core performance such as refractive index, dispersion control, high light transmittance retention and thermal stability, the optical glass in the existing technology is often difficult to fully meet the standards, and its refractive index is even more difficult to meet the specific needs of certain high-end applications.

[0003] Specifically, although the refractive index range of traditional optical glass is wide, its refractive index characteristics are insufficient when faced with tasks such as high-precision focusing, imaging, or optical signal transmission at specific wavelengths. Therefore, inventing a new type of optical glass with a higher refractive index and good dispersion control, high light transmittance and thermal stability is not only a breakthrough in the existing technical bottleneck, but also an urgent measure to promote the continuous advancement of optical technology and meet the high-performance requirements of future optical instruments. Summary of the invention

[0004] In view of the above-mentioned existing technical problems, the present invention aims to provide an optical glass with a high refractive index and a preparation method thereof. The optical glass prepared by this method has high tensile strength, high compressive strength, high corrosion resistance and chemical stability, and at the same time, the refractive index of the optical glass is further improved.

[0005] The present invention discloses an optical glass with a high refractive index, which is composed of the following components in weight ratio:

[0006] Silicon dioxide 40-60%; styrene 30-50%; selenium atoms 3-5%; sodium oxide 2-3%; potassium oxide 1-3%; calcium oxide 2-4%; barium oxide 1-2%; lead oxide 1-2%.

[0007] The present invention also discloses a method for preparing optical glass with a high refractive index, comprising the following process steps:

[0008] Preparation of S1 composite particles: Add silica to a high-temperature heat treatment furnace, heat it up to melt it, add selenium atoms to the high-temperature heat treatment furnace after the silica is completely melted, and then maintain the original temperature to continue the reaction for 1 to 2 hours, then cool down and add solvent and styrene, continue to stir after the addition is complete to cause a polymerization reaction, and after the reaction is completed, obtain polystyrene-coated silica-selenium composite particles;

[0009] S2 Preparation of optical glass: Add the composite particles obtained in step S1 to the glass kiln, heat up and melt, then add sodium oxide, potassium oxide, calcium oxide, barium oxide and lead oxide in sequence, continue to control the temperature and stir, after the reaction is completed, pour the molten mixture into shape, anneal, grind and polish, and finally obtain optical glass with a high refractive index.

[0010] Preferably, in the S1 composite particle preparation step, the heating and melting temperature of the high temperature heat treatment furnace is 1700-1800°C.

[0011] Preferably, in the step of preparing the S1 composite particles, the temperature needs to be lowered to 80-100°C.

[0012] Preferably, in the S1 composite particle preparation step, the mass ratio of styrene to solvent is 1:(5-10).

[0013] Preferably, in the step of preparing the S1 composite particles, the solvent is a mixture of propanol and deionized water, wherein the volume ratio of propanol to deionized water is 1:(1-2).

[0014] Preferably, in the step of preparing the S1 composite particles, the stirring speed of the polymerization reaction is 1200 to 1500 rpm; and the polymerization reaction time is 2 to 4 hours.

[0015] Preferably, in the S2 optical glass preparation step, the glass kiln needs to be heated to 1400-1700° C.; the temperature-controlled stirring time is 1-3 hours.

[0016] Preferably, in the S2 optical glass preparation step, pressure needs to be applied during the leaking molding process, and the applied pressure ranges from 100 to 300 MPa.

[0017] Preferably, in the S2 optical glass preparation step, during the annealing process, the optical glass pulling speed needs to be controlled to be 2-5 cm / min, and the optical glass discharge speed needs to be controlled to be 80-120 kg / h.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention provides an optical glass with a high refractive index, wherein the raw materials include silicon dioxide, styrene, selenium atoms, sodium oxide, potassium oxide, calcium oxide, barium oxide and lead oxide. Silicon dioxide, styrene and selenium atoms are prepared by a special preparation method to obtain composite particles of a core-shell structure of Se-SiO2-PS, and then the composite particles are melt-bonded with sodium oxide, potassium oxide, calcium oxide, barium oxide and lead oxide to obtain an optical glass with a high refractive index. The proportion of sodium oxide, potassium oxide, calcium oxide, barium oxide and lead oxide in the raw materials is strictly controlled, because adding them without controlling the proportion will reduce the chemical stability and mechanical properties of the optical glass.

[0020] The present invention also provides a method for preparing optical glass with a high refractive index, wherein selenium atoms are injected into a silicon dioxide substrate at a high temperature, and after the selenium atoms are completely combined with the silicon dioxide, styrene is added to carry out a polymerization reaction to form composite particles of a shell-core structure of Se-SiO2-PS; and then the composite particles are used as a base material to synthesize optical glass. The optical glass obtained by this method has high tensile strength, high compressive strength, high corrosion resistance and chemical stability, and further improves the refractive index of the optical glass. DETAILED DESCRIPTION

[0021] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0022] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0023] Embodiment 1: An optical glass with a high refractive index, comprising the following components in weight ratio:

[0024] Silicon dioxide 60%; styrene 30%; selenium atoms 3%; sodium oxide 2%; potassium oxide 1%; calcium oxide 2%; barium oxide 1%; lead oxide 1%.

[0025] A method for preparing optical glass with a high refractive index comprises the following steps:

[0026] Preparation of S1 composite particles: Add silica to a high-temperature heat treatment furnace, raise the temperature of the high-temperature heat treatment furnace to 1700°C, melt the silica in the furnace, and add selenium atoms to the high-temperature heat treatment furnace after the silica is completely melted, and then maintain the original temperature to continue the reaction for 1 hour, then lower the temperature of the high-temperature treatment furnace to 80°C, add solvent and styrene, the mass ratio of styrene to solvent is 1:5; the solvent is a mixture of propanol and deionized water, and the volume ratio of propanol to deionized water is 1:1; after the addition is completed, continue to stir to cause a polymerization reaction, the stirring rate of the polymerization reaction is 1200rpm, the polymerization reaction time is 2h, and after the reaction is completed, polystyrene-silicon dioxide-selenium composite particles are obtained.

[0027] Preparation of S2 optical glass: Add the composite particles obtained in step S1 to a glass kiln, heat the glass kiln to 1400°C and melt the composite particles. After the composite particles are completely melted, add sodium oxide, potassium oxide, calcium oxide, barium oxide and lead oxide in sequence. Continue to control the temperature at 1400°C and stir for 1 hour. After the reaction is completed, the molten mixture is leaked into shape, annealed, ground and polished. The pressure during the leaking and molding process is controlled at 100MPa, the optical glass pulling speed during the annealing process is 2cm / min, and the optical glass discharge speed is 80kg / h. Finally, optical glass with a high refractive index is obtained.

[0028] Embodiment 2: An optical glass with a high refractive index, comprising the following components in weight ratio:

[0029] Silicon dioxide 40%; styrene 50%; selenium atoms 3%; sodium oxide 2%; potassium oxide 1%; calcium oxide 2%; barium oxide 1%; lead oxide 1%.

[0030] A method for preparing optical glass with a high refractive index comprises the following steps:

[0031] Preparation of S1 composite particles: Add silica to a high-temperature heat treatment furnace, raise the temperature of the high-temperature heat treatment furnace to 1700°C, melt the silica in the furnace, and add selenium atoms to the high-temperature heat treatment furnace after the silica is completely melted, and then maintain the original temperature to continue the reaction for 1 hour, then lower the temperature of the high-temperature treatment furnace to 80°C, add solvent and styrene, the mass ratio of styrene to solvent is 1:5; the solvent is a mixture of propanol and deionized water, and the volume ratio of propanol to deionized water is 1:1; after the addition is completed, continue to stir to cause a polymerization reaction, the stirring rate of the polymerization reaction is 1200rpm, the polymerization reaction time is 2h, and after the reaction is completed, polystyrene-silicon dioxide-selenium composite particles are obtained.

[0032] Preparation of S2 optical glass: Add the composite particles obtained in step S1 to a glass kiln, heat the glass kiln to 1400°C and melt the composite particles. After the composite particles are completely melted, add sodium oxide, potassium oxide, calcium oxide, barium oxide and lead oxide in sequence. Continue to control the temperature at 1400°C and stir for 1 hour. After the reaction is completed, the molten mixture is leaked into shape, annealed, ground and polished. The pressure during the leaking and molding process is controlled at 100MPa, the optical glass pulling speed during the annealing process is 2cm / min, and the optical glass discharge speed is 80kg / h. Finally, optical glass with a high refractive index is obtained.

[0033] Embodiment 3: An optical glass with a high refractive index, comprising the following components in weight ratio:

[0034] Silicon dioxide 44%; styrene 37%; selenium atoms 5%; sodium oxide 3%; potassium oxide 3%; calcium oxide 4%; barium oxide 2%; lead oxide 2%.

[0035] A method for preparing optical glass with a high refractive index comprises the following steps:

[0036] Preparation of S1 composite particles: Add silica to a high-temperature heat treatment furnace, raise the temperature of the high-temperature heat treatment furnace to 1700°C, melt the silica in the furnace, and add selenium atoms to the high-temperature heat treatment furnace after the silica is completely melted, and then maintain the original temperature to continue the reaction for 1 hour, then lower the temperature of the high-temperature treatment furnace to 80°C, add solvent and styrene, the mass ratio of styrene to solvent is 1:5; the solvent is a mixture of propanol and deionized water, and the volume ratio of propanol to deionized water is 1:1; after the addition is completed, continue to stir to cause a polymerization reaction, the stirring rate of the polymerization reaction is 1200rpm, the polymerization reaction time is 2h, and after the reaction is completed, polystyrene-silicon dioxide-selenium composite particles are obtained.

[0037] Preparation of S2 optical glass: Add the composite particles obtained in step S1 to a glass kiln, heat the glass kiln to 1400°C and melt the composite particles. After the composite particles are completely melted, add sodium oxide, potassium oxide, calcium oxide, barium oxide and lead oxide in sequence. Continue to control the temperature at 1400°C and stir for 1 hour. After the reaction is completed, the molten mixture is leaked into shape, annealed, ground and polished. The pressure during the leaking and molding process is controlled at 100MPa, the optical glass pulling speed during the annealing process is 2cm / min, and the optical glass discharge speed is 80kg / h. Finally, optical glass with a high refractive index is obtained.

[0038] Embodiment 4: An optical glass with a high refractive index, comprising the following components in weight ratio:

[0039] Silicon dioxide 46.5%; styrene 39%; selenium atoms 4%; sodium oxide 2.5%; potassium oxide 2%; calcium oxide 3%; barium oxide 1.5%; lead oxide 1.5%.

[0040] A method for preparing optical glass with a high refractive index comprises the following steps:

[0041] Preparation of S1 composite particles: Add silica to a high-temperature heat treatment furnace, raise the temperature of the high-temperature heat treatment furnace to 1700°C, melt the silica in the furnace, and add selenium atoms to the high-temperature heat treatment furnace after the silica is completely melted, and then maintain the original temperature to continue the reaction for 1 hour, then lower the temperature of the high-temperature treatment furnace to 80°C, add solvent and styrene, the mass ratio of styrene to solvent is 1:5; the solvent is a mixture of propanol and deionized water, and the volume ratio of propanol to deionized water is 1:1; after the addition is completed, continue to stir to cause a polymerization reaction, the stirring rate of the polymerization reaction is 1200rpm, the polymerization reaction time is 2h, and after the reaction is completed, polystyrene-silicon dioxide-selenium composite particles are obtained.

[0042] Preparation of S2 optical glass: Add the composite particles obtained in step S1 to a glass kiln, heat the glass kiln to 1400°C and melt the composite particles. After the composite particles are completely melted, add sodium oxide, potassium oxide, calcium oxide, barium oxide and lead oxide in sequence. Continue to control the temperature at 1400°C and stir for 1 hour. After the reaction is completed, the molten mixture is leaked into shape, annealed, ground and polished. The pressure during the leaking and molding process is controlled at 100MPa, the optical glass pulling speed during the annealing process is 2cm / min, and the optical glass discharge speed is 80kg / h. Finally, optical glass with a high refractive index is obtained.

[0043] Embodiment 5: An optical glass with a high refractive index, comprising the following components in weight ratio:

[0044] Silicon dioxide 46.5%; styrene 39%; selenium atoms 4%; sodium oxide 2.5%; potassium oxide 2%; calcium oxide 3%; barium oxide 1.5%; lead oxide 1.5%.

[0045] A method for preparing optical glass with a high refractive index comprises the following steps:

[0046] Preparation of S1 composite particles: Add silica to a high-temperature heat treatment furnace, raise the temperature of the high-temperature heat treatment furnace to 1750°C, melt the silica in the furnace, and add selenium atoms to the high-temperature heat treatment furnace after the silica is completely melted, and then maintain the original temperature to continue the reaction for 1.5 hours, then lower the temperature of the high-temperature treatment furnace to 90°C, add solvent and styrene, the mass ratio of styrene to solvent is 1:7; the solvent is a mixture of propanol and deionized water, and the volume ratio of propanol to deionized water is 1:1.5; after the addition is completed, continue to stir to cause a polymerization reaction, the stirring rate of the polymerization reaction is 1350rpm, the polymerization reaction time is 3h, and after the reaction is completed, polystyrene-silicon dioxide-selenium composite particles are obtained.

[0047] Preparation of S2 optical glass: Add the composite particles obtained in step S1 to a glass kiln, heat the glass kiln to 1550°C and melt the composite particles. After the composite particles are completely melted, add sodium oxide, potassium oxide, calcium oxide, barium oxide and lead oxide in sequence. Continue to control the temperature at 1550°C and stir for 2 hours. After the reaction is completed, the molten mixture is leaked into shape, annealed, ground and polished. The pressure during the leaking and molding process is controlled at 200MPa, the optical glass pulling speed during the annealing process is 3.5cm / min, and the optical glass discharge speed is 100kg / h. Finally, optical glass with a high refractive index is obtained.

[0048] Embodiment 6: An optical glass with a high refractive index, comprising the following components in weight ratio:

[0049] Silicon dioxide 46.5%; styrene 39%; selenium atoms 4%; sodium oxide 2.5%; potassium oxide 2%; calcium oxide 3%; barium oxide 1.5%; lead oxide 1.5%.

[0050] A method for preparing optical glass with a high refractive index comprises the following steps:

[0051] Preparation of S1 composite particles: Add silica to a high-temperature heat treatment furnace, raise the temperature of the high-temperature heat treatment furnace to 1800°C, melt the silica in the furnace, and add selenium atoms to the high-temperature heat treatment furnace after the silica is completely melted, and then maintain the original temperature to continue the reaction for 2 hours, then lower the temperature of the high-temperature treatment furnace to 100°C, add solvent and styrene, the mass ratio of styrene to solvent is 1:10; the solvent is a mixture of propanol and deionized water, and the volume ratio of propanol to deionized water is 1:2; after the addition is completed, continue to stir to cause a polymerization reaction, the stirring rate of the polymerization reaction is 1500rpm, the polymerization reaction time is 4h, and after the reaction is completed, polystyrene-silicon dioxide-selenium composite particles are obtained.

[0052] Preparation of S2 optical glass: Add the composite particles obtained in step S1 to a glass kiln, heat the glass kiln to 1700°C and melt the composite particles. After the composite particles are completely melted, add sodium oxide, potassium oxide, calcium oxide, barium oxide and lead oxide in sequence. Continue to control the temperature at 1700°C and stir for 2 hours. After the reaction is completed, the molten mixture is leaked into shape, annealed, ground and polished. The pressure during the leaking and molding process is controlled at 300MPa, the optical glass pulling speed during the annealing process is 5cm / min, and the optical glass discharge speed is 120kg / h. Finally, optical glass with a high refractive index is obtained.

[0053] Embodiment 7: An optical glass with a high refractive index, comprising the following components in weight ratio:

[0054] Silicon dioxide 46.5%; Styrene 39%; Sodium oxide 2.5%; Potassium oxide 2%; Calcium oxide 3%; Barium oxide 1.5%; Lead oxide 1.5%.

[0055] A method for preparing optical glass with a high refractive index comprises the following steps:

[0056] Preparation of S1 composite particles: Add silica to a high-temperature heat treatment furnace, raise the temperature of the high-temperature heat treatment furnace to 1750°C, melt the silica in the furnace, and add selenium atoms to the high-temperature heat treatment furnace after the silica is completely melted, and then maintain the original temperature to continue the reaction for 1.5 hours, then lower the temperature of the high-temperature treatment furnace to 90°C, add solvent and styrene, the mass ratio of styrene to solvent is 1:7; the solvent is a mixture of propanol and deionized water, and the volume ratio of propanol to deionized water is 1:1.5; after the addition is completed, continue to stir to cause a polymerization reaction, the stirring rate of the polymerization reaction is 1350rpm, the polymerization reaction time is 3h, and after the reaction is completed, polystyrene-silicon dioxide-selenium composite particles are obtained.

[0057] Preparation of S2 optical glass: Add the composite particles obtained in step S1 to a glass kiln, heat the glass kiln to 1550°C and melt the composite particles. After the composite particles are completely melted, add sodium oxide, potassium oxide, calcium oxide, barium oxide and lead oxide in sequence. Continue to control the temperature at 1550°C and stir for 2 hours. After the reaction is completed, the molten mixture is leaked into shape, annealed, ground and polished. The pressure during the leaking and molding process is controlled at 200MPa, the optical glass pulling speed during the annealing process is 3.5cm / min, and the optical glass discharge speed is 100kg / h. Finally, optical glass with a high refractive index is obtained.

[0058] Embodiment 8: An optical glass with a high refractive index, comprising the following components in weight ratio:

[0059] Silicon dioxide 46.5%; selenium atoms 4%; sodium oxide 2.5%; potassium oxide 2%; calcium oxide 3%; barium oxide 1.5%; lead oxide 1.5%.

[0060] A method for preparing optical glass with a high refractive index comprises the following steps:

[0061] Preparation of S1 composite particles: Add silica to a high-temperature heat treatment furnace, raise the temperature of the high-temperature heat treatment furnace to 1750°C, melt the silica in the furnace, and add selenium atoms to the high-temperature heat treatment furnace after the silica is completely melted, and then maintain the original temperature to continue the reaction for 1.5 hours, then lower the temperature of the high-temperature treatment furnace to 90°C, add solvent and styrene, the mass ratio of styrene to solvent is 1:7; the solvent is a mixture of propanol and deionized water, and the volume ratio of propanol to deionized water is 1:1.5; after the addition is completed, continue to stir to cause a polymerization reaction, the stirring rate of the polymerization reaction is 1350rpm, the polymerization reaction time is 3h, and after the reaction is completed, polystyrene-silicon dioxide-selenium composite particles are obtained.

[0062] Preparation of S2 optical glass: Add the composite particles obtained in step S1 to a glass kiln, heat the glass kiln to 1550°C and melt the composite particles. After the composite particles are completely melted, add sodium oxide, potassium oxide, calcium oxide, barium oxide and lead oxide in sequence. Continue to control the temperature at 1550°C and stir for 2 hours. After the reaction is completed, the molten mixture is leaked into shape, annealed, ground and polished. The pressure during the leaking and molding process is controlled at 200MPa, the optical glass pulling speed during the annealing process is 3.5cm / min, and the optical glass discharge speed is 100kg / h. Finally, optical glass with a high refractive index is obtained.

[0063] The optical glasses prepared in Examples 1 to 8 were tested for performance, and the test results are shown in the following table:

[0064] Example Refractive Index Tensile strength(MPa) Compressive strength(MPa) pH=10 Is it corrosive? 1 1.79 65 94 no 2 1.78 66 96 no 3 1.80 68 99 no 4 1.81 71 103 no 5 1.85 76 110 no 6 1.82 67 97 no 7 1.65 59 85 yes 8 1.50 55 80 yes

[0065] Examples 1 to 4 and Examples 7 to 8 are screenings of the raw material ratio; Examples 4 to 6 are screenings of the preparation conditions. It can be seen from the data in the above table that the optical glasses prepared in Examples 1 to 6 all have good refractive index, tensile strength, compressive strength and corrosion resistance, among which the experimental conditions and raw material ratios of Example 5 are the best. Compared with Example 5, Example 7 does not add selenium atoms to the raw materials, and Example 8 does not add styrene to the raw materials. The refractive index, tensile strength, compressive strength and corrosion resistance of Examples 7 to 8 are lower than those of Examples 1 to 6. This is because the optical glasses prepared in Examples 7 to 8 do not generate the core-shell structure of Se-SiO2-PS, so the chemical stability, mechanical properties and refractive index will be reduced.

[0066] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. An optical glass with a high refractive index, characterized in that: It is composed of the following ingredients in weight ratio: Silicon dioxide 40-60%; styrene 30-50%; selenium atoms 3-5%; sodium oxide 2-3%; potassium oxide 1-3%; calcium oxide 2-4%; barium oxide 1-2%; lead oxide 1-2%.

2. A method for preparing optical glass with a high refractive index, characterized in that: The following steps are involved: Preparation of S1 composite particles: Add silica to a high-temperature heat treatment furnace, heat it up to melt it, add selenium atoms to the high-temperature heat treatment furnace after the silica is completely melted, and then maintain the original temperature to continue the reaction for 1 to 2 hours, then cool down and add solvent and styrene, continue to stir after the addition is complete to cause a polymerization reaction, and after the reaction is completed, obtain polystyrene-coated silica-selenium composite particles; S2 Preparation of optical glass: Add the composite particles obtained in step S1 to the glass kiln, heat up and melt, then add sodium oxide, potassium oxide, calcium oxide, barium oxide and lead oxide in sequence, continue to control the temperature and stir, after the reaction is completed, pour the molten mixture into shape, anneal, grind and polish, and finally obtain optical glass with a high refractive index.

3. The method for preparing an optical glass with a high refractive index according to claim 2, characterized in that: In the S1 composite particle preparation step, the heating and melting temperature of the high temperature heat treatment furnace is 1700-1800°C.

4. The method for preparing an optical glass with a high refractive index according to claim 2, characterized in that: In the step of preparing the S1 composite particles, the temperature needs to be lowered to 80-100°C.

5. The method for preparing an optical glass with a high refractive index according to claim 2, characterized in that: In the S1 composite particle preparation step, the mass ratio of styrene to solvent is 1:(5-10).

6. The method for preparing an optical glass with a high refractive index according to claim 2, characterized in that: In the S1 composite particle preparation step, the solvent is a mixture of propanol and deionized water, wherein the volume ratio of propanol to deionized water is 1:(1-2).

7. The method for preparing an optical glass with a high refractive index according to claim 2, characterized in that: In the S1 composite particle preparation step, the stirring speed of the polymerization reaction is 1200-1500 rpm; the polymerization reaction time is 2-4 hours.

8. The method for preparing an optical glass with a high refractive index according to claim 2, characterized in that: In the S2 optical glass preparation step, the glass kiln needs to be heated to 1400-1700° C.; the temperature-controlled stirring time is 1-3 hours.

9. The method for preparing an optical glass with a high refractive index according to claim 2, characterized in that: In the S2 optical glass preparation step, pressure needs to be applied during the leak molding process, and the applied pressure ranges from 100 to 300 MPa.

10. The method for preparing an optical glass with a high refractive index according to claim 2, characterized in that: In the S2 optical glass preparation step, during the annealing process, the optical glass pulling speed needs to be controlled to be 2 to 5 cm / min, and the optical glass discharge speed needs to be controlled to be 80 to 120 kg / h.

Citation Information

Patent Citations

  • Novel glass handicraft processing technology

    CN111533451A

  • Optical glass, optical element and preform for precision press molding

    JP2009203140A

  • Optical power limiting material

    US20020024752A1